Bonhoeffer as Youth Worker: A Theological Vision for Discipleship and Life Together - Lie, Ronny (Jurnal Youth Ministry (2013-2016), 2015)
Bonhoeffer as Youth Worker: A Theological Vision for Discipleship and Life Together